2012
DOI: 10.1007/s10457-012-9551-3
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic differences between young longleaf-pine silvopasture and open-pasture

Abstract: Information is needed relative to changes that occur in microclimatic conditions in the early stages of open-pasture to pine silvopasture conversion in the Southeastern USA. This research tested the hypothesis that microclimatic conditions would vary between young-pine silvopasture and open-pasture. The research was conducted in a longleaf-pine (Pinus palustris Mill.)-bahiagrass (Paspalum notatum Flugge) silvopasture and adjacent open bahiagrass pasture at Americus, Georgia. Longleaf-pine was planted in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Given that trees in an agricultural system provide modifications to air temperature, water vapor content, relative humidity, PAR, and wind velocity (Jose, Gillespie, & Pallardy, 2004;Karki & Goodman, 2013), and stimulate higher biodiversity in both above-and belowground flora and fauna (Bainard et al, 2012;De Beenhouwer, Aerts, & Honnay, 2013), we expected the agroforestry systems to contribute to resistance and resilience of AMF to water limitation. While it has been shown that trees and crops can harbor the same species of AMF (Ingelby, Wilson, Munro, & Cavers, 2007), further research is needed to assess to the role of trees in maintaining AMF and other beneficial F I G U R E 5 Nonmetric multidimensional scaling (NMDS) ordinations for fungal communities in an agroforest (panels a and b) and monoculture (panels c and d).…”
Section: Discussionmentioning
confidence: 99%
“…Given that trees in an agricultural system provide modifications to air temperature, water vapor content, relative humidity, PAR, and wind velocity (Jose, Gillespie, & Pallardy, 2004;Karki & Goodman, 2013), and stimulate higher biodiversity in both above-and belowground flora and fauna (Bainard et al, 2012;De Beenhouwer, Aerts, & Honnay, 2013), we expected the agroforestry systems to contribute to resistance and resilience of AMF to water limitation. While it has been shown that trees and crops can harbor the same species of AMF (Ingelby, Wilson, Munro, & Cavers, 2007), further research is needed to assess to the role of trees in maintaining AMF and other beneficial F I G U R E 5 Nonmetric multidimensional scaling (NMDS) ordinations for fungal communities in an agroforest (panels a and b) and monoculture (panels c and d).…”
Section: Discussionmentioning
confidence: 99%
“…Microclimatic measures (ambient temperature, relative humidity, soil moisture, and PAR) indicate environmental conditions in OP were more stressful than in silvopasture treatments. Ambient temperature and PAR tend to be lower under tree canopies compared with open systems [31], and past studies have reported cooler microclimatic conditions in silvopasture versus OP [3,4,32,33]. The BSP and HSP silvopasture systems used in this study provided shade and lowered the PAR and ambient temperature within the system compared with OPs with no canopy cover.…”
Section: Microclimatic Conditionmentioning
confidence: 72%
“…For example, agroforestry can reduce the net loss in long-wave radiation from plant surfaces and protect plants from radiation frosts locally [32], alleviate drought stress of the crop [33,34], and alter the temperature, with positive and negative effects on the crop depending on the growth stage [33]. Agroforestry can further alter surface roughness and thus airflows [35], with potential effects on plant productivity through the reduction of wind speed [33,36], and reduce evapotranspiration of the crop [37] with potential effects of the tree age [38].…”
Section: Climate Regulationmentioning
confidence: 99%